Language use and choice in Jember-Javanese speakers: a study on intercultural communication - Alies Poetri Lintangsari (UPT P2M Politeknik Negeri Malang, 2013)
This study tries to answer questions (a) which languages are used in language contact, Javanese, Indonesia, Madura or English, (b) what is the language choices found in the conversation, (c) what are the motives behind the language use and choice, and (d) what is the influence of social factors on the language use and language choice? Using, among others, Scollon and Scollon’s (2000,2001) theory, the writer answers the questions. The people in Jember use Bahasa Jemberan to communicate among sub-ethnis groups. Most of language used in dialogue is Jemberan such as the usage of koen and awakdewe refers to pronoun you and us. This dialect mixes Javanese, Indonesian, Madurese, and even English. Some motives found of the usage the language choice by code switching and code mixing, the topic shifting signalize the shifting of language. For instance, if the speakers recounted their story, they tended to use Bahasa Indonesia, while they tried to quote and imitate their lecturers they would choose Bahasa Indonesia or English. And when the topic shift into commenting or gossiping, they tended to use Jember Javanesse, in some cases, Jember Javanesse also used to show solidarity. Some influencing factors on the language use and choice are participants’ background and topics of conversation.